Diversity of Home Garden Plants in Traditional Tourism Villages - Keswari Krisnandika, Anak Agung; Kohdrata, Naniek; Agus Dharmadiatmika, I Made; Korri Arisena, Gede Mekse; Joanna Gawryszewska, Beata (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 17 No 2 (2023): Vol 17 No 2 (2023)DO - 10.24843/SOCA.2023.v17.i02.p05, 2023)
Socio-cultural shifts and environmental changes can cause changes in the composition of plants in the home garden. These changes may lead to the loss of uniquely valuable plants in the home garden. Therefore, this study aims to identify species and functions; diversity and similarity as well as the composition of home garden plants in three traditional Balinese tourism villages. The method used was a survey with observation data collection techniques, questionnaires, and interviews. There were a total of 90 samples of home gardens from three traditional tourism villages in Bali with different landscape characteristics, namely Tenganan Pegringsingan, Pengotan, and Julah villages. They were selected as survey locations to record plant diversity. The results of this study show that the plants in the home gardens of the three villages have the main function as ornaments plants. Plants in both Tenganan Pegringsingan and Julah Villages have a high diversity of species, while those in Penggotan Village are considered as the medium category. The differences in plant species in each location indicate that the owners’ culture also has an influence in addition to environmental factors